2018
DOI: 10.1021/acscentsci.8b00240
|View full text |Cite
|
Sign up to set email alerts
|

Taming the Strength of Interfacial Interactions via Nanoconfinement

Abstract: The interaction between two immiscible materials is related to the number of contacts per unit area formed by the two materials. For practical reasons, this information is often parametrized by the interfacial free energy, which is commonly derived via rather cumbersome approaches, where properties of the interface are described by combining surface parameters of the single materials. These combining rules, however, neglect any effect that geometry might have on the strength of the interfacial interaction. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 37 publications
6
64
0
Order By: Relevance
“…Through these relationships, the partial desorption of copolymer adsorbed layers in the presence of hydrogen‐bonding solvents can grant valuable insight into polymer‐substrate interactions, since the relative change to copolymer h ads with washing reflects a corresponding change to its number of individual contacts with the substrate. The evidence that the number of polymer‐substrate adsorbed contacts is influenced by the film's surrounding environment is consistent with the work of Simavilla et al, which related the change in number of contacts and thickness resulting of adsorbed layers to system‐specific effective Hamaker constants 33…”
Section: Figuresupporting
confidence: 90%
See 4 more Smart Citations
“…Through these relationships, the partial desorption of copolymer adsorbed layers in the presence of hydrogen‐bonding solvents can grant valuable insight into polymer‐substrate interactions, since the relative change to copolymer h ads with washing reflects a corresponding change to its number of individual contacts with the substrate. The evidence that the number of polymer‐substrate adsorbed contacts is influenced by the film's surrounding environment is consistent with the work of Simavilla et al, which related the change in number of contacts and thickness resulting of adsorbed layers to system‐specific effective Hamaker constants 33…”
Section: Figuresupporting
confidence: 90%
“…Predictions by Guiselin32 and supporting experiments20,33 have demonstrated that h ads of a given polymer is directly proportional to its number of monomers directly and indirectly adsorbed to the substrate, both of which scale with N 1/2 , where N is the polymer's degree of polymerization. This adsorbed amount, for a given polymer and molecular weight, is then directly proportional to the quantity of individual contacts at the substrate 33.…”
Section: Figurementioning
confidence: 92%
See 3 more Smart Citations